1997
DOI: 10.1073/pnas.94.9.4757
|View full text |Cite
|
Sign up to set email alerts
|

The antibipolar drug valproate mimics lithium in stimulating glutamate release and inositol 1,4,5-trisphosphate accumulation in brain cortex slices but not accumulation of inositol monophosphates and bisphosphates

Abstract: Valproic acid and lithium are effective antibipolar drugs. We recently showed that lithium stimulated the release of glutamate in monkey and mouse cerebral cortex slices, which, through activation of the N-methyl-D-aspartate receptor, increased accumulation of inositol 1,4,5-trisphosphate [Ins(1,4,5)P 3 ]. We show here that valproate behaves similarly to lithium in that at therapeutic concentrations it stimulates glutamate release and Ins(1,4,5)P 3 accumulation in mouse cerebral cortex slices. The fact that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 21 publications
1
41
0
3
Order By: Relevance
“…As described in the Materials and Methods section, the CA 3 pyramidal neurons are activated by quisqualate, hence, it is important to mention that lithium can also affect glutamate neurotransmission. In fact, it has been shown that lithium blocks the uptake of glutamate from cerebral cortex slices of monkey and mouse (Dixon et al 1994;Dixon and Hokin 1997). Moreover in the , rats treated with imipramine for 21 days (10 mg/kg/ day, SC, IMI), rats treated with imipramine and having a lithium diet (IMI ϩ Li ϩ ), rats treated with tranylcypromine for 21 days (2.5 mg/kg/day, SC, TCP), rats treated with tranylcypromine and having a lithium diet (TCP ϩ Li ϩ ), rats treated with paroxetine for 21 days (10 mg/kg/day, SC, PRX) and rats treated with paroxetine and having a lithium diet (PRX ϩ Li ϩ ).…”
Section: Discussionmentioning
confidence: 99%
“…As described in the Materials and Methods section, the CA 3 pyramidal neurons are activated by quisqualate, hence, it is important to mention that lithium can also affect glutamate neurotransmission. In fact, it has been shown that lithium blocks the uptake of glutamate from cerebral cortex slices of monkey and mouse (Dixon et al 1994;Dixon and Hokin 1997). Moreover in the , rats treated with imipramine for 21 days (10 mg/kg/ day, SC, IMI), rats treated with imipramine and having a lithium diet (IMI ϩ Li ϩ ), rats treated with tranylcypromine for 21 days (2.5 mg/kg/day, SC, TCP), rats treated with tranylcypromine and having a lithium diet (TCP ϩ Li ϩ ), rats treated with paroxetine for 21 days (10 mg/kg/day, SC, PRX) and rats treated with paroxetine and having a lithium diet (PRX ϩ Li ϩ ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that valproate does not inhibit bovine brain (16) or yeast inositol monophosphatase activity (17) and has a minimal effect on receptor-mediated phosphoinositide turnover (18). In addition, valproate does not lead to large accumulations of inositol mono-or bisphosphates, as seen with lithium (19).…”
mentioning
confidence: 96%
“…Inhibition of this reaction by valproate is further supported by the observation that the opi1 mutant does not exhibit increased resistance to valproate, despite constitutive expression of INO1 and increased levels of Ins-1-P synthase (30). Previous findings that valproate does not inhibit inositol monophosphatase or cause an accumulation of inositol phosphates (16,19) have been cited as evidence against the inositol-depletion hypothesis. The experiments shown in this report indicate that valproate does indeed cause inositol depletion.…”
mentioning
confidence: 99%
“…Furthermore, lithium and VPA can down-regulate expression of protein kinase C isoforms PKC␣ and PKC⑀, induce expression of the anti-apoptotic gene bcl-2, and activate AP-1-dependent transcription (through a direct effect on c-jun activity and by increasing expression of c-Jun (11,12)). Both VPA and lithium also stimulate glutamate release and inositol 1,4,5-trisphosphate accumulation in mouse cerebral cortex slices, although apparently through distinct mechanisms (14). Furthermore, both VPA and lithium have been shown to confer protection from neurotoxic agents (15)(16)(17).…”
mentioning
confidence: 99%